Utilization of waste glass as a replacement for fine aggregates in controlled low strength materials (CLSM) - Hajim, Marshery H.
Controlled low Strength Material (CLSM) is a mixture of aggregates (sand, gravel, or both), cement and water. The mix designs vary with the required properties of application. In this study, the mixture is designed to replace 0, 10, 20, 30 and 40% of fine aggregates with glass. The objective of this study is to utilize and assess the properties of CLSM using waste glass as partial replacement for fine aggregates. Common CLSM properties has been checked. These are the Compressive Strength, Excavatability, Flowability, and Unit Weight. These properties are then compared to the standard values for certain applications. It was concluded that the glass replaced is inversely proportional to compressive strength and unit weight and directly proportional to flowability. All mixtures are not excavatble since all of them exceeded 200 psi requirement. Also, 0% and 10% are significantly different to 30 and 40% glass replacement on the 28-day compressive strength. It can be concluded that all the mixtures are not recommended to be used for pipe embedment since all mixtures are not excavatable. It can also be concluded that the properties checked conform to the standards of applications such as backfill, structural fill and pavement base. Other properties that are required and recommended to be checked.